African city- Cape Town in pieces/aesthetics, theories, narratives, fragments - Inggs, Alice (Michaelis School of Fine Art, 2014)
Six sections, six ways of reading African cities and, by extension, Africa. Anchored in the Cape Town metropolis - an important node in both North?South and South?South global trade networks ? this project investigates the African urban as a site of knowledge production. Rather than attempt to capture a complete or panoramic vision of Cape Town, this project is instead a non-linear narrative of the city space constructed out of a combination of essays, narrative fragments, reportage, images and formal and informal interviews. Starting with what makes an African city "African" in African City, the investigation moves through five more thematic categories: Built Environment;; Renewal/Decay;; Everyday Urbanism;; Nature;; and Pattern. Out of each section new ways of reading the city emerge ? through architectural surfaces;; the city as archive;; pop culture;; ecology;; and design. This project is about curating and creating an analytical topography of a specific urban space in Africa;; but it is also about engaging with the urban on an experiential level. Readers are encouraged to engage in a dialogue with the urban form, to trace the contours of the city space. The textual and visual material contained within the project is rendered into building blocks, which can be rearranged into various visions of the city, transferring agency to the reader to create their own interpretation of (this) city space. This interactive element manifests an important idea underpinning the project: there are multiple lines of flight emanating from the supposed fixed grid of the post-colonial or post-apartheid city space;; the urban narrative can be rewritten;; Africa can be reimagined. Ultimately, this project is an experiment in and juxtaposition of modes of analysis, advancing new ways of reading African urban forms ? from Africa.